Asset Recovery in Eradication Illicit Enrichment : Indonesia with the United States and South Korea - Nainggolan, Jesella Ramayanti; Esther, July; Debora, Debora (Formosa Journal of Science and Technology, 2024)
This research discusses the importance of asset recovery in combating illicit enrichment in Indonesia, with a comparison to the United States and South Korea. Where the level of illicit enrichment has become crucial in this country. The study's goal is to examine asset recovery laws and practices and pinpoint ways that Indonesia might improve. The method used is a literature study with comparative analysis of regulations and practices in the three countries. The results show that Indonesia faces significant challenges in asset recovery, while the United States and South Korea have more comprehensive legal frameworks. The conclusion of this study recommends strengthening the legal system and passing an asset forfeiture bill to increase the effectiveness of corruption eradication in Indonesia.